2006
DOI: 10.1677/joe.1.06226
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the phosphatidylinositol 3-kinase/protein kinase B pathway in the ovary of rats by chronic treatment with hCG and insulin

Abstract: Polycystic ovary syndrome (PCOS) manifests as chronic anovulation, ovarian hyperandrogenism, and follicular cysts, which are amplified by insulin as well as the inability of the hormone to stimulate glucose uptake in classic target tissues such as muscle and fat. In the present study, we evaluated the regulation of the insulin-signaling pathways by using immunoprecipitation and immunoblotting in whole extracts of ovaries from non-pregnant human chorionic gonadotropin (hCG)-treated rats, hyperinsulinemic-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
5
14
0
Order By: Relevance
“…The typical follicular cells hardly were recognized. In some cysts, the inner wall consisted of the luteinized cells, which was consistent with the finding reported by a recent study in the same model (21). Furthermore, ovaries possessing cystic follicles also displayed an enhanced proportion of stromal-interstitial tissue (Fig.…”
Section: Ovary Morphologysupporting
confidence: 91%
See 1 more Smart Citation
“…The typical follicular cells hardly were recognized. In some cysts, the inner wall consisted of the luteinized cells, which was consistent with the finding reported by a recent study in the same model (21). Furthermore, ovaries possessing cystic follicles also displayed an enhanced proportion of stromal-interstitial tissue (Fig.…”
Section: Ovary Morphologysupporting
confidence: 91%
“…Previous data demonstrated that insulin has been found to increase LH-driven cyclic adenosine monophosphate accumulation and enhance theca cell steroidogenesis (31). Moreover, Lima et al (21) showed that insulin þ hCG increased the tyrosine phosphorylation of insulin receptor substrates, resulting in the increased associations of insulin receptor substrate-1 and insulin receptor substrate-2 with p85 phosphatidylinositol 3-kinase, followed by enhanced Akt phosphorylation in the ovary. In this way, insulin þ hCG treatment may lead finally to the up-regulation of GSK-3, which may be involved in augmentation of steroidogenesis, as we have assessed in the present work.…”
Section: Figure 3 Continuedmentioning
confidence: 96%
“…Female mice that lack crucial components of the insulin signaling pathway, such as IRS2, are infertile and display ovarian and hypothalamic function deficits, suggesting that the IRS2 pathway mediates the insulin effects upon the reproductive function (Burks et al 2000). In insulin resistance conditions, such as the polycystic ovary syndrome, the ovary remains sensitive to insulin, whereas other organs exhibit a significant reduction in insulin action (Poretsky 1991, Lima et al 2006. Since deficits of insulin receptor signaling in the muscle, liver, and adipose tissue are related to obesityassociated insulin resistance, and as it is known that these deficits occur through tissue-and pathway-specific factors, it is interesting to evaluate if the ovary from obese female rats remains sensitive to insulin concomitantly with enhancement of progesterone levels, and alteration of estrous cycle and of ovarian morphology.…”
Section: Discussionmentioning
confidence: 99%
“…We used a rat model in which PCOS-like features can be induced by a combination of insulin and human chorionic gonadotropin (hCG) (Chen et al, 2009, Damario et al, 2000, Li et al, 2013, Lima et al, 2006, Poretsky et al, 1992, Zhang et al, 2016). In this model, the AR-regulated transcriptional program, PI3K–Akt–NFκB–FoxO1, and the AMPK signaling pathways were measured, including implantation-related gene signature expression.…”
Section: Introductionmentioning
confidence: 99%